Implementation of Covid-19 Response Policies from a Religious Perspective at Darussalam Islamic Boarding School, South of Kalimantan, Indonesia - Jamaluddin, Jamaluddin; Muthahari, Muhammad; Al Syahrin, M Najeri (Technium Social Sciences Journal, 2022)
Islamic boarding schools are educational institutions that have the characteristic of having dormitories, students who are referred to as santri can not be separated from the activities of life in Islamic boarding schools for 24 hours. By carrying out face-to-face activities, of course, Islamic boarding schools must have carried out careful consideration of the worst possible risks that will be faced. For example, the emergence of a new cluster in the pesantren environment affects students, administrators, and even caregivers. The dormitory capacity which is generally limited, the facilities for bathing, washing, shared latrines, and the limited quantity of environmental sanitation of the pesantren are certain things that need attention. In general, the purpose of this study is to find out what policies or decisions are taken by the Darussalam Martapura Islamic Boarding School, especially at high schools, in the learning process of preventing Covid-19 in 2020-2021. In addition, it also seeks to find out how the implementation of the policy is seen from the aspects of communication, sources, especially the economic resources of the community or the economic conditions of the community, in addition to those owned by educational institutions, as well as the tendencies or behavior of the community and implementers. The results of this study indicate that in the context of the policies carried out by Islamic boarding schools in the implementation of the Covid-19 response policies in 2020-2021 from a religious perspective, it has been successfully implemented. The limits of ability from a social and economic point of view of some students found some information related to the limits of the willingness or ability of the students to carry out policies related to the efforts made in overcoming the spread of Covid-19 in the Islamic boarding school environment here including students and students and alumni who have provided information related to the limits of the ability to implement this policy because there is no coercion and pressure from both Islamic boarding schools and teachers, what is required is to increase piety.